2012
DOI: 10.1371/journal.pone.0032125
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Alveolar Epithelial Cells in Initiating and Shaping Pulmonary Immune Responses: Communication between Innate and Adaptive Immune Systems

Abstract: Macrophages and dendritic cells have been recognized as key players in the defense against mycobacterial infection. However, more recently, other cells in the lungs such as alveolar epithelial cells (AEC) have been found to play important roles in the defense and pathogenesis of infection. In the present study we first compared AEC with pulmonary macrophages (PuM) isolated from mice in their ability to internalize and control Bacillus Calmette-Guérin (BCG) growth and their capacity as AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 37 publications
4
83
0
Order By: Relevance
“…Furthermore, Thorley et al (11) showed that other factors, such as IL-8 and GRO-␣, also are important, as neutralizing these chemokines reduced monocyte migration toward culture medium from primary human type II AEC by 39% and 51%, respectively (11). We have previously published that in our system, AEC secrete high levels of MCP-1 and the murine IL-8 homologs KC and MIP-2 upon stimulation with LPS (20). It is thus likely that these factors play a major role in inducing the macrophage migration in our system.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Furthermore, Thorley et al (11) showed that other factors, such as IL-8 and GRO-␣, also are important, as neutralizing these chemokines reduced monocyte migration toward culture medium from primary human type II AEC by 39% and 51%, respectively (11). We have previously published that in our system, AEC secrete high levels of MCP-1 and the murine IL-8 homologs KC and MIP-2 upon stimulation with LPS (20). It is thus likely that these factors play a major role in inducing the macrophage migration in our system.…”
Section: Discussionmentioning
confidence: 59%
“…Upon activation, AEC secrete a number of chemokines, including keratinocyte cytokine (KC), monocyte chemoattractant protein (MCP-1), and MIP-2␣ (20). To determine whether AEC promote migration of pulmonary cells and whether a specific cell type is preferentially influenced by AEC-derived factors, we set up a Transwell migration assay, using total lung cells as responder cells, and let these migrate toward supernatants from either AEC sup or AEC LPS .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purified CD4 + T cells (1.5 × 10 6 cells per milliliter) were treated with soluble anti-CD3 (3 μg/mL) or recombinant human IL-2 (20 ng/mL; R&D Systems) with or without L-Kyn (300 μM) in a 96-well plate (Corning Costar) at 37°C for 72 h. During the final 15∼17 h, the cells were pulsed with [ Isolation of Alveolar Epithelial Cells. Primary alveolar epithelial cells were isolated as previously described (48). In brief, dispase (Gibco-Invitrogen) was instilled into lung tissues of C57BL/6 mice via the trachea.…”
Section: Methodsmentioning
confidence: 99%